Validity of critical thinking skills instrument on prospective Mathematics teachers - Ayu Faradillah; Sabila Adlina (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This study aims to describe the process of validity of critical thinking skills on prospective mathematics teachers. This research used a quantitative approach with a survey method. Data were collected from 245 prospective mathematics teachers from 19 Mathematics education study programs at 19 higher education institutions in Indonesia. The data were collected using a questionnaire given via Google Form and analyzed by the Rasch Model analysis using Winstep software and Confirmatory Factor Analysis (CFA) using JASP. The results show that the instrument of critical thinking skills with indicators such as open-mindedness, inquisitiveness, systematicity, truth-seeking, analyticity, and self-confidence is valid and reliable, although it has to consider eliminating items and person misfit.